Using Abdominal Binder for Reducing Postoperative Wound Pain After Cesarean Delivery: A randomized controlled trial - Thanyarat Singdaeng; Ussanee Sangkomkamhang; Thananit Sangkomkamhang (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To determine the effect of using abdominal binder after cesarean delivery on postoperative wound pain, physical function and analgesic drugs use.Materials and Methods: A randomized controlled trial was conducted between January and April 2018 at KhonKaen Hospital. Fifty women who underwent elective cesarean delivery were randomly allocated to either the abdominal binder group or routine standard care. The primary outcome was postoperative wound pain as measured by a visual analog scale (VAS) scores at 6, 24, and 48 hours after using the binder. The secondary outcomes included physical function as measured by distance 6-minute walk test (6MWT), time to first ambulation, analgesic drugs use and adverse effects.Results: Postoperative wound pain was indicated by a significantly lower VAS score in the binder group with the repeated measures ANOVA (F= 30.78, p < 0.005). The respective postoperative VAS score at 6, 24, and 48 hours was also significantly lower in the binder group (mean ± SD at 6, 24, and 48 hr. = 4.77 ± 1.97, 3.73 ± 1.48, and 2.51 ± 1.63 vs. standard care 6.85 ± 2.26, 5.49 ± 2.34, and 4.66 ± 2.21; p < 0.05). Postoperative opioid drugs use in the binder group was significantly less than in the standard care (5.22 ± 1.20 mg vs. 7.63 ± 2.43 mg; p < 0.01). There were no significant differences in the 6MWT and time to first ambulation between the two groups. No serious adverse effects were reported.Conclusion: Using abdominal binder can reduced pain and analgesic drugs used in postoperative cesarean delivery.